2005
DOI: 10.1111/j.1365-2605.2005.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SpanX proteins in normal testes and in testicular germ cell tumours

Abstract: We investigated the expression of the SpanX protein family in cells of normal testes and in testicular germ cell tumours, mainly seminomas and embryonal carcinomas, using an immunohistochemical approach. Most of the normal germ cells, belonging to spermatogonial and primary spermatocytic classes, showed a strong nuclear positivity. In contrast, post-meiotic germ cells showed diffused cytoplasmic and sometimes also perinuclear localization of the signal. The vast majority of cells were also positive in eight se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…13 In addition, SPANX-A/D genes expression has recently been shown in testicular germ cells tumors. 6,7 Recently Salemi et al 14 showed the association of a specific gene dosage classes of SPANX-C gene and melanomas. These observations suggested that SPANX-A/D genes, or some of them, may be involved in melanoma development.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 In addition, SPANX-A/D genes expression has recently been shown in testicular germ cells tumors. 6,7 Recently Salemi et al 14 showed the association of a specific gene dosage classes of SPANX-C gene and melanomas. These observations suggested that SPANX-A/D genes, or some of them, may be involved in melanoma development.…”
Section: Introductionmentioning
confidence: 98%
“…Among them, the sperm protein associated with the nucleus in the X chromosome (SPANX) gene family is present. [5][6][7] It includes 2 subfamilies, SPANX-N (SPANX-N1, -N2, -N3, -N4, and -N5) 8 and SPANX-A/D (SPANX-A1/-A2/-B/-C/-D) (human genome build 36.2). The SPANX-N subfamily is the ancestral form, which gave rise to the SPANX-A/D subfamily in the hominoid lineage.…”
Section: Introductionmentioning
confidence: 99%
“…SPANX genes encode the cancer-testis class of antigens [Westbrook et al 2004] and extensive protein antibody analysis provides evidence that expression of the human gene family is limited to the testis and malignant tumors [Salemi et al 2004[Salemi et al , 2006Westbrook et al 2000;Zendman et al 2003]. Little is understood, however, about the exact function of the individual SPANX genes.…”
Section: Introductionmentioning
confidence: 99%
“…All SPANX proteins, except SPANXC, are found exclusively in germ cells, and all the SPANX proteins, except SPANXB, are found at some level in various tumor cells. Current understanding of the role of the SPANX protein during spermatogenesis is still incomplete [Martínez-Heredia et al 2006], but there is consensus that SPANX genes are expressed throughout spermatogenesis, from sperm cell precursors to ejaculated spermatozoa [Salemi et al 2004[Salemi et al , 2006Westbrook et al 2000;. To date the role of SPANX gene variation with male fertility has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SPANX genes are deregulated in Down's syndrome subjects who have undescended testis and an increased risk of TGCTs (Satge et al, 1997), further suggesting interaction of genes located on chromosome X and chromosome 21 for TGCT susceptibility. SPANX genes have a testis-specific expression that is conserved in rodents and humans, and was also detected in EC clusters and TGCTs (Westbrook et al, 2004;Salemi et al, 2006).…”
Section: Sex Chromosomes and Tgctsmentioning
confidence: 99%